SELF-EFFICATION AS THE DETERMINANTS FOR THE INTENTION OF ENTREPRENEURSHIP - Rachma Rizqina Mardhotillah; Denis Fidita Karya; Candraningrat (Journal of Applied Management and Business, 2020)
This examination intends to decide: (1) The degree of self-adequacy of undergraduate management study programs in Surabaya, (2) The degree of enterprising expectations of undergraduate management study programs in Surabaya, (3) The impact of self-viability on undergraduate management study programs in Surabaya. The number of population in this examination is the undergraduate management study programs in Surabaya. The testing system utilizes Proportionate Stratified Random Sampling and acquired an example of 167 undergraduate management study programs in Surabaya. The instrument preliminary utilized master judgment and proceeded with preliminaries on 30 undergraduate management study programs in Surabaya. Validity test in this research utilizes the Product Moment connection method from Pearson. Unwavering quality test utilizing the Cronbach Alpha. Information gathering utilizes a survey that is dispersed straightforwardly and through electronic media. The investigation essential testing incorporates typicality test and linearity test. The information investigation method utilized is straightforward relapse to test theories.